PENGARUH SALES GROWTH, CAPITAL INTENSITY, DAN RISIKO PERUSAHAAN TERHADAP TAX AVOIDANCE - Indawati Indawati; Anggun Anggraini; Endang Ruhiyat (AKUA: Jurnal Akuntansi dan Keuangan, 2025)
This study aims to examine, analyze, and measure the effect of Sales Growth, Capital Intensity, and Firm Age on Tax Avoidance in industrial sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020 until 2024. This research is classified as quantitative research, which aims to describe and test predetermined hypotheses using secondary data. The data analysis method employed is panel data regression using Microsoft Excel and EViews 9 applications. The population in this study includes all companies in the industrial sector. The data collection technique used is purposive sampling, in which out of 50 population units, 14 were selected as research samples. The results of the study show that Sales Growth, Capital Intensity, and Firm Risk simultaneously have a significant effect on Tax Avoidance in industrial sector companies for the period 2020 until 2024. Partially, Sales Growth has a significant effect on Tax Avoidance, Capital Intensity has no effect on Tax Avoidance, while Firm Risk has a significant effect on Tax Avoidance..